Relation between reversal dominance time and carrying capacities in multiplex ecological ammensalism - A numerical study - Acharyulu, K.V.L.N; Sailaja, M Lakshmi; Mohan, P Rama (Journal of Experimental Sciences, 2012)
The paper aims to investigate a mathematical model of multiplex Ecological Ammensalism with the help of classical RK-method of fourth order in view of reversal dominance time. The mathematical model constitutes of Ammensal-enemy species pair with cover protection for Ammensal species, alternative resources for enemy species and both the species are immigrated. In addition to this, harvesting variable rates are also incorporated. The model is characterized by a couple of first order non linear ordinary differential equations. The relation between the carrying capacity of Ammensal /enemy species with the reversal dominance time is investigated numerically. Some conclusions are derived from the relationships. AMS Classification: 92 D 25, 92 D 40